Development of an E-Book on Traditional Cosmetics and Beverages for SPA Treatments - Ika Pranita Siregar; Christine Ulina Tarigan; Nolis Marliati; Tri Wulaningrum (Indonesian Health Journal, 2026)
This study is motivated by the increasing global demand for digital learning media in vocational education, particularly in fields requiring strong practical and visual understanding, such as beauty and spa therapy. Traditional instructional materials are often insufficient to support competency-based learning in courses involving cosmetic formulation and traditional spa treatments. Therefore, this research aims to develop and evaluate an interactive e-book on traditional cosmetics and beverages for spa treatment using the ADDIE model. The study employed a Research and Development (R&D) approach following the ADDIE stages — Analysis, Design, Development, Implementation, and Evaluation. The study involved subject matter experts, media experts, linguists, and 30 vocational students as respondents. Data were collected through questionnaires, interviews, observations, and documentation, and analysed using descriptive quantitative and qualitative methods. The results showed that the developed e-book achieved very high validity and feasibility scores, with expert validation ratings exceeding 95% and an average user response score above 92%. The e-book was considered highly effective in terms of content quality, language clarity, visual design, usability, and accessibility. In conclusion, the interactive e-book on traditional cosmetics and spa treatment is feasible and effective as a learning medium in vocational education. It enhances student engagement, supports independent learning, and bridges theoretical knowledge with practical skills, while integrating local wisdom into digital learning resources.